2023
DOI: 10.3390/ijms24054541
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transplant Immunology and Intestinal Graft Rejection: From Basic Mechanisms to Potential Biomarkers

Abstract: Intestinal transplantation (ITx) remains a lifesaving option for patients suffering from irreversible intestinal failure and complications from total parenteral nutrition. Since its inception, it became obvious that intestinal grafts are highly immunogenic, due to their high lymphoid load, the abundance in epithelial cells and constant exposure to external antigens and microbiota. This combination of factors and several redundant effector pathways makes ITx immunobiology unique. To this complex immunologic sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Conforme destacado por Morán et al (2023), o tratamento para a amebíase apresenta uma variabilidade nas opções terapêuticas devido à diversidade de formas clínicas e à gravidade dos sintomas. Predominantemente, a amebíase é tratada com amebicidas, que se dividem em duas categorias: luminais e sistêmicos.…”
Section: Resultsunclassified
“…Conforme destacado por Morán et al (2023), o tratamento para a amebíase apresenta uma variabilidade nas opções terapêuticas devido à diversidade de formas clínicas e à gravidade dos sintomas. Predominantemente, a amebíase é tratada com amebicidas, que se dividem em duas categorias: luminais e sistêmicos.…”
Section: Resultsunclassified
“…Decreased citrulline was reported to reflect reduced enterocyte mass and intestinal insufficiency during acute rejection [11,26,27]; increased fecal calprotectin implicated ongoing immune responses in the intestine [28]. However, the lack of diagnostic specificity had limited their application in diagnosing acute rejection [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The quest for acute rejection-specific biomarkers is a challenging endeavor. Low specificity in differentiating acute rejection from enteritis complicates conclusive outcomes [31]. Due to the dispersed distribution of samples representing enteritis and sepsis outcomes within our patient cohort, we opted not to include these groups in our GEE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, treatment with RSPO3 prior to I/R injury was found to decrease immune cell infiltration into the lamina propria by maintaining tight endothelial adherens junctions ( Kannan et al, 2013 ). I/R injury deprives an intestinal region of oxygen and later renourishes the tissue with oxygen to replicate the pathophysiology underlying a multitude of intestinal conditions that disrupt the gut barrier, including IB, necrotizing enterocolitis (NEC), IBD, and intestinal transplantation ( Gubernatorova et al, 2016 ; Rumbo and Oltean, 2023 ). Hypoxic injury initiates at the villus tip and spreads down to the proliferative crypt ( Shepherd, 1982 ; Blikslager et al, 1997 ), but the intrinsic regenerative ability of the intestine must keep up with epithelial cell death to prevent bloodstream susceptibility to bacteria ( Williams et al, 2015 ).…”
Section: Lymphangiocrine Factors That Mediate Intestinal Epithelium R...mentioning
confidence: 99%